Ameliorate QSPR Study of Alkyl Hydroperoxides - Romanelli, Gustavo Pablo (2001)
A set of linear and nonlinear functions of one and several variables are determined to predict refractive index, molar refraction, and density for a representative set of alkyl hydroperoxides. Quite satisfactory predictions can be made on the basis of these equations and in some cases it is necessary to resort to higher-order equations to get a very good quantitative description of physical properties. Some possible further extensions of this study are pointed out in order to get a step head in the understanding of the quan- titative structure-property relationships of alkyl hydroperoxides.